Intervensi Psikososial sebagai Upaya Peningkatan Kesejahteraan Mental Warga Binaan Lapas Perempuan Kelas IIA Palembang - Angeline Mareta Sihite; Anindya Syifa Khairunnisa; Rheisya Gravitha Maharani; Puspita Sari (Altifani Journal: International Journal of Community Engagement, 2025)
The mental well-being of inmates is often hindered by various psychosocial pressures such as stress, aggressiveness, low self-acceptance, and pessimism about the future. This study aims to enhance the psychological well-being of inmates through psychosocial interventions conducted at the Palembang Class IIA Women’s Correctional Institution. The program began with an assessment through observation, interviews, and surveys to identify four major psychosocial issues. Based on the assessment results, four types of interventions were developed, including psychoeducation based on Cognitive Behavioral Therapy (CBT), expressive arts therapy, forgiveness therapy, reality therapy, and active psychoeducation sessions. Each intervention was conducted in two face-to-face sessions involving a total of 26 selected participants. The pre-test and post-test results indicated an increase in participants’ knowledge and understanding of the psychological concepts delivered, followed by more adaptive behavioral changes in managing emotions, fostering self-compassion, accepting oneself, and developing a positive outlook toward the future. Overall, the findings demonstrate that psychosocial intervention can serve as an effective strategy to improve inmates’ mental well-being and readiness for social reintegration.